Estimating Loads of Pollution in the Lake Dam AL Basel Using Better Assessment Science Integrating Point and Nonpoint Sources (BASINS) - سلمان هناء; جعفر رائد; مرهج احمد (Latakia University Journal -Engineering Sciences Series, 2021)
Lake Al-Basel Dam is one of the most important water source on the Syrian coast, and this lake is exposed to many sources of pollution resulting from human activities, which includes point sources such as municipal and industrial discharge, and non-point sources such as runoff from agricultural lands. Many models were used to estimate pollution from different sources in watersheds. In this study, the PLOAD model within the BASINS program was used to estimate the pollution load resulting from non-point sources on an average annual basis. The lake watershed was divided into (20) sub-basins based on the digital elevation model DEM and given them written signs from "A" to "T", and the land use map was defined within the watershed of the study area, and the annual rainfall value along with the runoff rate for it were entered. The results showed that the total annual pollution load coming from the sub-basins of both the total nitrogen reached (2406.1kg/y) and the total phosphorus (549.93kg/y). Sub-basins (A, G, Q) are the major contributors to the annual pollution load reaching the lake and they are estimated for total nitrogen (456.37, 239.74, 219.19) kg/y respectively and for total phosphorus as (103.7, 54.75, 50.06) kg/y respectively, and it was found that the agricultural land category is the dominant one within the sub-basins mentioned above. Where the percentage of agricultural land within the sub-basin (A) is (68%) off the basin area and estimated at (20) million square meters. From the foregoing, is showed that agricultural lands are one of the main sources of pollution load coming from watersheds.